2006
DOI: 10.1016/j.biopsych.2006.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Altered Prefrontal Cortical Metabolic Response to Mesocortical Activation in Adult Animals with a Neonatal Ventral Hippocampal Lesion

Abstract: Background-Adult animals with a neonatal ventral hippocampal lesion (NVHL) exhibit deficits in working memory and sensorimotor gating similar to those observed in schizophrenia. As cognitive deficits in this disorder are typically associated with changes in cortical metabolic levels, we investigated here whether an NVHL affects metabolic responses to ventral tegmental area (VTA) activation, a procedure that elicits abnormal cell firing in the prefrontal cortex (PFC) of NVHL animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…A similar non-linear relationship was observed in schizophrenia but with increases at low working memory loads and a decrease in metabolic activity with loads that would engage the PFC of control subjects (Manoach 2003). The PFC metabolic responses to different intensities of VTA stimulation were tested in both sham and NVHL animals with cytochrome oxidase I staining, revealing a leftward shift only in post-pubertal animals that had received a bilateral NVHL (Tseng et al 2006a). A functional magnetic resonance imaging study has also revealed increased blood flow in several brain regions, including the PFC, in NVHL animals (Risterucci et al 2005).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…A similar non-linear relationship was observed in schizophrenia but with increases at low working memory loads and a decrease in metabolic activity with loads that would engage the PFC of control subjects (Manoach 2003). The PFC metabolic responses to different intensities of VTA stimulation were tested in both sham and NVHL animals with cytochrome oxidase I staining, revealing a leftward shift only in post-pubertal animals that had received a bilateral NVHL (Tseng et al 2006a). A functional magnetic resonance imaging study has also revealed increased blood flow in several brain regions, including the PFC, in NVHL animals (Risterucci et al 2005).…”
Section: Discussionmentioning
confidence: 52%
“…A deficit in PFC interneurons has indeed been suggested by the selective downregulation of glutamate decarboxylase-67 messenger RNA in the PFC of NVHL animals (Lipska et al 2003a(Lipska et al , 2003b. This, compounded by the abnormal potentiation of D 1 and NMDA responses and the attenuation of D 2 inhibition of AMPA responses, would yield a hyper-reactive PFC in NVHL animals, especially in response to mesocortical stimulation Tseng et al 2006a). Thus, PFC DA-GABA-glutamate interactions are compromised in animals that received an early inactivation of the hippocampal formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined 33 rats with a bilateral ventral hippocampal lesion with substantial rostro-caudal extension, similar to other such studies (Chambers et al, 1996;Becker et al, 1999;Khaing et al, 2000;Swerdlow et al, 2001;Goto and O'Donnell, 2002;Le Pen and Moreau, 2002;O'Donnell et al, 2002;Bhardwaj et al, 2003;Le Pen et al, 2003;Wood et al, 2003;Laplante et al, 2004Laplante et al, , 2005Flores et al, 2005;Risterucci et al, 2005;Conroy et al, 2007;Tseng et al, 2006Tseng et al, , 2007Tseng et al, , 2008Tseng et al, , 2009Bertrand et al, ). This was concluded from the histological aspect of the lesions (not shown).…”
Section: Discussionmentioning
confidence: 90%
“…Recent work shows that there is hyperactivity of CA1 in this model and that this hyperactivity affects downstream processes Grace 2007, 2011). Notably, the hippocampus can activate the dopamine system via polysynaptic pathways (Lodge and Grace 2011), which, in turn, affects prefrontal function (Tseng et al 2006). Importantly, a high-resolution study of the hippocampal blood oxygenation level-dependent (BOLD) signal in schizophrenia shows a particularly strong activation in CA1 (Schobel et al 2009).…”
mentioning
confidence: 99%